Natural management of social capital, is it an economic alternative for vulnerability of the middle class in Monterrey Nuevo León, México? - Leal Iga, Jorge (2019)
Although there is an important middle class in Mexico, its members are primarily citizens who live just above the poverty line, and are vulnerable to at least one type of social deprivation, in addition to low incomes. Given that it is impossible for this population to reach higher income levels in the country, this investigation focused on the study of the natural management of social capital as an alternative for the middle class to achieve partial substitution of the benefits people could obtain from the economic capital that it lacks.